Collagenolytic activity of conjunctival fluid in healthy people and patients with aseptic ulcer of the cornea of various etiologies - Brzheskaya I.V.; Somov E.E (РМЖ "Клиническая офтальмология")
Brzheskaya I.V.1,2, Somov E.E.1,3 1 St. Petersburg State Pediatric Medical University 2 St. Petersburg City Mariinsky Hospital 3 S. Fyodorov Eye Microsurgery Federal State Institution, St. Petersburg brunch The development and progression of an aseptic corneal ulcer is largely determined by the activity of proteolytic enzymes in the corneal stroma. And since it reflects the collagenolytic activity of the conjunctival fluid, its evaluation is of great practical and scientific interest. Aim: to study the proteolytic activity of the conjunctival fluid in patients with aseptic ulcer of the cornea of various etiologies. Patients and Methods: conjunctival fluid of healthy people and patients with corneal ulcer (31 persons, 37 eyes), divided into 3 groups, was studied. Group 1 included patients (16) with systemic diseases: with Sjögren, Stevens-Johnson syndromes and rosacea; group 2 — patients (10) after herpetic keratitis; group 3 — patients (5) with a paralytic lagophthalmos after removal of cerebellopontile angle schwannoma. An integral evaluation of the collagenolytic activity of the conjunctival fluid was made by estimating the drying rate of its mixture with collagen gel in a ratio of 1:1, directly dependent on the activity of the proteolytic enzymes contained in it. Results: the norm limits (M±2m) of the collagenolytic activity of the conjunctival fluid of healthy people were determined: 176KE/ml — 212KE/ml. The most pronounced activity was characterized by a conjunctival fluid of patients with systemic diseases: it was the highest in patients with Sjörgen syndrome — 852.3±22.7 KE/ml (4.4 times higher than normal) and slightly lower (815.7±21.9 KE/ml) in patients with Stevens-Johnson syndrome. It was significantly lower in paralytic lagophthalmos (482.4±21.4 KE/ml), but 2.5 times higher than normal limits (p <0.001). Conclusion: the collagenolytic activity of the conjunctival fluid of patients with corneal aseptic ulcers is on average 150–340% higher than in healthy individuals and depends on the depth and etiology of the ulcer. It is the highest in patients with Sjögren and Stevens-Johnson syndromes. Studies are worthwhile to develop ways to reduce collagenolytic aggressiveness in patients with corneal pathology accompanied by a pronounced lysis process. Key words: lacrimal fluid, activity of proteolytic enzymes, dry eye syndrome, Sjorgren’s syndrome, corneal aseptic ulcer, diagnosis of progression. For citation: Brzheskaya I.V., Somov E.E. Collagenolytic activity of conjunctival fluid in healthy people and patients with aseptic ulcer of the cornea of various etiologies. RMJ “Clinical ophthalmology”. 2018;2:77–80.